Preservation the Sundanese Wewengkon Kuningan Language Through Android-Based Educational Games - Jaelani, Asep Jejen; Hikmat, Ade; Safi’i, Imam (Journal of Ecohumanism, 2025)
This study explores the development and evaluation of Android-based educational games specifically designed to preserve the Sundanese language in the Kuningan region. This study uses mixed methods, this study combines in-depth literature review with empirical evaluation to assess the effectiveness of games in the context of language learning. These educational games are designed with local and cultural needs in mind, offering a contextual and engaging learning experience for users. The results of the study show that this game not only succeeded in significantly improving Sundanese language skills, but also contributed positively to the preservation of Sundanese language and culture. These findings underscore the potential of educational games as an effective tool in language education, emphasizing the importance of integrating local cultures in the learning process. This research highlights how technology and game design can play an important role in supporting the preservation of traditional languages and cultures in the digital era.